Self-Efficacy of English Department Students in Writing Bachelor’s Theses - Kurnia Rahman; Amirullah Abduh; Chairil Anwar Korompot (Journal of Excellence in English Language Education, 2022)
The aims of this research are to find out the level of students’ self-efficacy based on the self-efficacy aspect during the process of writing bachelor’s theses and the students’ ways to improve their self-efficacy during the process of writing bachelor’s theses process. This research used mixed method, which means that qualitative and quantitative were used in this research. In this article only contains the first research question which used quantitative method.   The data of this research was collected through an online questionnaire. The sample of this research were decided by using purposive sampling technique. There were 30 students from class A of the 2018 cohorts of the English Language Education Study Program (PSPBI) at State University of Makassar who participated in online questionnaire then there are 6 students participated in online interview. The result of data analysis found that (1) most of the students were in medium level of self-efficacy (73.3%) and the rest of the students in the high self-efficacy level (26.7%).